Struktura bohaterów "Lilli Wenedy" Juliusza Słowackiego - Chachulska, Marta (Colloquia Litteraria, 2020)
The article focuses on issues of the structure of the romantic drama and construction of its characters. Lilla Weneda – a pseudo-mythological display of the creation of Polish nation is based on the idea of duality in every possible field. The essay shows how this idea is present in construction of every scene and the whole drama – particularly through the protagonists, their conversations and personalities. Both destructive and fruitful clash of two tribes occurs mostly through collisions of theirs individuals. And – as the new nation is built of two different tribes, in every scene two different persons are creating a completely new quality by matching their characteristics. The symmetry and assymetry in the collisions gives special dynamics that makes this human architecture so fascinating.